Self-Reported Childhood Maltreatment and Traumatic Events among Israeli Patients Suffering from Fibromyalgia and Rheumatoid Arthritis. (11th January 2017) - Hellou, Raneen; Häuser, Winfried; Brenner, Inbal; Buskila, Dan; Jacob, Giris; Elkayam, Ori; Aloush, Valerie; Ablin, Jacob N.
Abstract : Objective . The association between Fibromyalgia Syndrome (FMS) and childhood maltreatment and adversity has frequently been proposed but limited data exists regarding the transcultural nature of this association. Methods . 75 Israeli FMS patients and 23 Rheumatoid Arthritis (RA) patients were compared. Childhood maltreatment was assessed by the Childhood Trauma Questionnaire (CTQ) and potential depressive and anxiety disorders were assessed by the Patient Health Questionnaire-4. FMS severity was assessed by the Widespread Pain Index (WPI), the Symptom Severity Score (SSS), and the FIQ. PTSD was diagnosed according to the DSM IV. RA severity was assessed by the RA Disease Activity Index. Health status was assessed by the SF-36. Results. Similar to reports in other countries, high levels of self-reported childhood adversity were reported by Israeli FMS patients. PTSD was significantly more common among FMS patients compared with RA patients, as well as childhood emotional abuse and physical and emotional neglect. Levels of depression and anxiety were significantly higher among FMS patients. Conclusion . The study demonstrated the cross cultural association between FMS and childhood maltreatment, including neglect, emotional abuse, and PTSD. Significant differences were demonstrated between FMS patients and patients suffering from RA, a model of an inflammatory chronic rheumatic disease.